Prevalence of Eosinophilic Esophagitis in Patients with Gastroesophageal Reflux Symptoms: A Cross-Sectional Study - Noor Ul Amin, Azhar Saeed, Syed Mir Usman Shah, Saadia Zainab, Moeenul Huq, Muhammad Shuaib (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:Prevalence of eosinophilic esophagitis in patients with gastroesophageal reflux symptoms. Study Design:A Cross-sectional Study Place and Duration:The study was conducted at Gastroenterology department of DHQ Teaching Hospital, Timargarafor six months from August 2021 to January 2022. Methods: There were 300 patients of both genders presented in this study. Individuals who agreed to participate, their personal information such as age, gender, height and weight was recorded with their informed permission. Included patients were had gastroesophageal reflux symptoms. Esophageal biopsies of all the patients were underwentesophagogastroduodenoscopy (EGD). Prevalence of eosinophilic esophagitis was recorded among all cases. SPSS 23.0 was used to analyze all data. Results: The mean age of the patients was 41.9±8.21 years and had mean BMI 25.7±6.31 kg/m2. Majority of the patients were males 190 (63.3%) and 110 (36.7%) were females. We found that frequency of eosinophilic esophagitis among all cases were 27 (9%). Among 27 cases of EoE, males were higher in number 19 (70.4%) than females 8 (29.6%). Among these cases, heartburn was the most common symptom found in 10 (37.03%) cases, followed by dysphagia in 6 (22.2%), epigastric pain in 5 (18.5%). Lower esophagus found in 12 (44.4%) cases and mid in 15 (55.6%) cases. Mean eosinophils was 24.4±7.29 per HPF. As per histological findings,eosinophilicmicroabscess was found in 20 (70.1%) cases. Conclusion:Patients with refractory GERD are at risk of developing eosinophilic esophagitis, which can be life-threatening. Dysphagia, heartburn, and food impaction are all possible symptoms. The EoE screening of elderly patients with prolonged GERD, atopy, and non-response to stomach acid inhibitors must be evaluated.